Influence of Benefits Realization Management on Business Strategies and Project Success in Pakistan's Construction Projects - Shakir Hafeez; Shahid Hussain; Yasir Javed; Bilal Bin Saeed (International Review of Management and Marketing, 2016)
Benefits realization management (BRM) practices are supposed to be the one of the key promising solution for developing business strategies and for project success. This concept is evaluated in the perspective of Pakistan's construction industry where the project managers keen to develop the business strategies in order to reduce the gap between effective planning and project executions. The objective of the study is to examine the impact of BRM practices on business strategies and project success in the Pakistan's construction industry. The project success measured by the project output, project goals and the project customer, while BRM practices measured by the project planning, project review, project realization and project strategy. The results of Model 1 show the influence of success dimension factors on project success which reveals that, out of four dimension factors, 3 success factors positively associated with the project success, while schedule goals have a negative relationship with the project success. The results of Model -11 show the influence of BRM practices on project success in three different regression paths. In the first regression path, 7 BRM item shows their significant relationship with the project success, out of which 2 of them having a negative relationship with the project success while remaining 5 of them having a positive relationship with the project success. In the second regression path, out of four BRM factors, three have a positive relationship with the project success, while the remaining BRM factor shows a negative association with the project success. Finally, in the third regression path, the aggregated value of BRM practices tends to show the positive relationship with the project success in the Pakistan's construction projects. The results of Model -111 indicate BRM practices have a positive relationship with the business strategy in the construction industry; however, the intensity of BRM practices is comparatively low to influence business strategy as compared to larger influence of BRM practices on project success. The study conclude that BRM practices deem desirable for project success i.e., there is required a strong policy vista to device policies in order to strengthen the capabilities of project managers to fore see the future challenges across the construction industry.